2015
DOI: 10.1177/1087057114559490
|View full text |Cite
|
Sign up to set email alerts
|

High-Content Phenotypic Screening and Triaging Strategy to Identify Small Molecules Driving Oligodendrocyte Progenitor Cell Differentiation

Abstract: Multiple Sclerosis is a demyelinating disease of the CNS and the primary cause of neurological disability in young adults. Loss of myelinating oligodendrocytes leads to neuronal dysfunction and death and is an important contributing factor to this disease. Endogenous oligodendrocyte precursor cells (OPCs), which on differentiation are responsible for replacing myelin, are present in the adult CNS. As such, therapeutic agents that can stimulate OPCs to differentiate and remyelinate demyelinated axons under path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…However, 5 days after plating with two applications of RNS60, we detected higher numbers O4 and MBP expressing cells under RNS60 treatment compared to control medium (N1) condition. We believe our results are in line with many other studies that have attempted pharmacological promotion of OPCs differentiation 32 33 . Finally, RNS60 did not alter the rate of OPC proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…However, 5 days after plating with two applications of RNS60, we detected higher numbers O4 and MBP expressing cells under RNS60 treatment compared to control medium (N1) condition. We believe our results are in line with many other studies that have attempted pharmacological promotion of OPCs differentiation 32 33 . Finally, RNS60 did not alter the rate of OPC proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Phenotypic screens are enjoying something of a renaissance in terms of projects aimed at identifying interventions to treat diseases of the CNS (Prior et al, ; Pruss, ). Indeed, eight studies to date have taken the broadly similar approach of screening compound libraries for their ability to promote the differentiation of oligodendrocytes in vitro (Deshmukh et al, ; Joubert et al, ; Lariosa‐Willingham et al, ; Mei et al, ; Najm et al, ; Peppard et al, ; Porcu et al, ) (Table ). The results of these studies have already generated new compounds and targets of great promise (see Tables , ).…”
Section: Phenotypic Screens To Discover Mechanisms To Promote Remyelimentioning
confidence: 99%
“…Each of the eight in vitro OPC differentiation screens employed some form of automated analysis. Six of the eight screens were carried out using simple oligodendrocyteenriched 2D cultures grown in multiwell plate format, with automated image acquisition(Deshmukh et al, 2013; Joubert et al, 2010;Lariosa- Willingham et al, 2016;Najm et al, 2015;Peppard et al, 2015;Porcu et al, 2015).Subsequent image analyses included relatively simple quantification of DAPI-positive nuclei surrounded by MBP staining, as used by Deshmukh et al, to serve as a proxy for oligodendrocyte differentiation. In contrast, both Najm et al, and Lariosa-Willingham employed more complex analyses of cell morphology to estimate myelin produced per MBP-expressing oligodendrocyte, in addition to assessing differentiation.…”
mentioning
confidence: 99%
“…The fact that many demyelinated lesions contain OPCs that do not differentiate has prompted efforts to identify strategies to promote oligodendrocyte differentiation. Indeed, recent unbiased phenotypic screens have led to the identification of several hit compounds that promote oligodendrocyte differentiation in vitro ( Deshmukh et al, 2013 ; Joubert et al, 2010 ; Mei et al, 2014 ; Mei et al, 2016 ; Najm et al, 2015 ; Peppard et al, 2015 ; Porcu et al, 2015 ). A number of these hits have been validated in vivo ( Cole et al, 2017 ), and one, clemastine, has even shown efficacy in improving optic nerve function in patients with MS ( Green et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%